Evolution and characteristics of COVID-19 panemia in Peru - Garmendia-Lorena, Fausto (2021)
Objective: To show the evolution and characteristics of  SARS-Cov2 pandemia in Peru from april 5th to september 30th, 2020. Material and methods: In an observational, descriptive, retrospective and longitudinal study, informatión from the Peruvian Ministry of Health, COVID-19 Situational Room, warnigs from the National Epidemiology Center, Prevention and Disease Control and the Panamerican Health Organization (PAHO), from april 05th to september 30th 2020 concerning to the SARS-Cov2 pandemia in Peru were analysed. Results: In this period of time, 818,297 persons were infected, 32535 died and 690528 recovered from the disease, the letality index was 3,34 % and mortality rate per 100,000 inhabitants was 27,65. Peru is the third most affected country by the pandemia in South America and its incidence first growed up overwhelming the health facilities and now it is lowering. The prevalence along the country is heterogeneous, it is lower in the mountain departaments than in the coast and jungle ones, related to geographic and social factors; this pandemia has produced very serious health, economic and social problems. Conclusions: The SARS-Cov2 pandemia has produced a very strong impactc on the Peruvian health, economy social status, demonstrating that it is very vulnerable country to this type of health situations.